2014
DOI: 10.1080/10426914.2013.792428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brazing Filler and Method on ITER Thermal Anchor Joint Crack

Abstract: Thermal anchor, one of the key components to keep temperature balance of gravity magnet support, should be avoided welding defects in its welding joints, which endure large forces when the international thermonuclear experimental reactor (ITER) fusion device is operating. The influences of brazing fillers and brazing methods on the cracks in joints of thermal anchor were investigated by microstructure analysis. The results have shown that the copper penetrating cracks were observed in the heat-affected zone (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Copper-austenite and tin-steel are both brittle couples; the liquid-solid compound process of Sn bronze/steel dissimilar metals is susceptible to LME cracks, leading to bearing failure as a fatigue crack source during service. [8][9][10][11][12] For the Sn bronzesteel system, electroplating Ni onto a steel substrate is a common approach for suppressing LME cracks; however, this technique has some drawbacks, including high cost, high energy consumption, complex procedure, a restricted welding processing window, and limited LME cracks inhibition efficacy. [13] It is feasible to suppress LME cracks by introducing a Cu-Ni alloy interlayer, but this method needs to be coupled with certain manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…Copper-austenite and tin-steel are both brittle couples; the liquid-solid compound process of Sn bronze/steel dissimilar metals is susceptible to LME cracks, leading to bearing failure as a fatigue crack source during service. [8][9][10][11][12] For the Sn bronzesteel system, electroplating Ni onto a steel substrate is a common approach for suppressing LME cracks; however, this technique has some drawbacks, including high cost, high energy consumption, complex procedure, a restricted welding processing window, and limited LME cracks inhibition efficacy. [13] It is feasible to suppress LME cracks by introducing a Cu-Ni alloy interlayer, but this method needs to be coupled with certain manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…Cu-SS is a well-known LME couple which has been investigated by many researchers. They concluded that the tension state of SS and the intimate contact between them are the main formative factors for LME [7,9,13]. However, the research on the effect of stress intensity during Cu-SS LME cracking is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, the research on the effect of stress intensity during Cu-SS LME cracking is rarely reported. Up to now, vacuum brazing has appeared to be a good and reliable choice for joining SS with copper alloy without LME cracking, which is attributed to the lower stress caused by the lower temperature gradient during brazing [13,14]. But does LME cracking occur when SS is brazed with copper-based filler in vacuum under tension stress?…”
Section: Introductionmentioning
confidence: 99%